2005
DOI: 10.1111/j.1478-3231.2005.1118.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced uptake of lactosaminated human albumin by rat hepatocarcinomas: implications for an improved chemotherapy of primary liver tumors

Abstract: The present results suggest that in the chemotherapy of HCCs expressing the ASGP-R the extra-hepatic toxicity of anticancer agents can be reduced by conjugation to L-HSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…The results of the Two-dimensional echocardiography was performed on all groups 14 weeks after injection of DENA. Data obtained from these images show increased % ejection fraction (a) and % fractional area change (b) in rats treated with resveratrol; however, changes were not significant [63]. Our histological study also shows significant pathological changes, indicating frequent occurrence of preneoplastic lesions in the livers of DENAinitiated rats.…”
Section: Discussionmentioning
confidence: 54%
“…The results of the Two-dimensional echocardiography was performed on all groups 14 weeks after injection of DENA. Data obtained from these images show increased % ejection fraction (a) and % fractional area change (b) in rats treated with resveratrol; however, changes were not significant [63]. Our histological study also shows significant pathological changes, indicating frequent occurrence of preneoplastic lesions in the livers of DENAinitiated rats.…”
Section: Discussionmentioning
confidence: 54%
“…9 Highly proliferative tumor cells were shown to present intracytoplasmic albumin deposits. 10 Another study confirmed that malign tumors are able to internalize albumin through endocytosis which is further processed in lysosomes. 11 The resulting amino acids are further used for the synthesis of various substrates needed for tumor growth.…”
Section: Introductionmentioning
confidence: 88%
“…As experimental model of human HCC, we used rats treated with DEN which induces poor, moderate and well differentiated forms of HCCs with histological features similar to those of the human tumors [6].…”
Section: Introductionmentioning
confidence: 99%